2010
DOI: 10.1128/jcm.01801-09
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Testing in the Clinical Laboratory by Use of Multiple Testing Algorithms

Abstract: The incidence of Clostridium difficile infection (CDI) has risen almost 3-fold in the United States over the past decade, emphasizing the need for rapid and accurate tests for CDI. The Cepheid Xpert C. difficile assay is an integrated, closed, nucleic acid amplification system that automates sample preparation and real-time PCR detection of the toxin B gene (tcdB). A total of 432 stool specimens from symptomatic patients were tested by a glutamate dehydrogenase (GDH) assay, a toxin A and B enzyme immunoassay (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
148
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(162 citation statements)
references
References 33 publications
10
148
1
3
Order By: Relevance
“…1 However, this approach often requires several days to complete, and neither assay is commonly available in clinical laboratories. The recent comprehensive study of C. difficile detection methods, 2 which reported the sensitivity of a commonly used GDH assay as 87.6% when compared with toxigenic culture, is consistent with concerns of falsely GDH-negative samples raised by the report of Larson et al 48 NovakWeekley et al 34 reported that initial GDH screening failed to identify approximately 15% of samples containing toxigenic C. difficile isolates. In addition, the mean sensitivity of membrane-type GDH assays in the ESCMID survey was only 60% when compared with toxigenic culture, 3 suggesting that GDH screening may not be as highly sensitive as previously assumed.…”
Section: Gdh Assaysmentioning
confidence: 64%
See 4 more Smart Citations
“…1 However, this approach often requires several days to complete, and neither assay is commonly available in clinical laboratories. The recent comprehensive study of C. difficile detection methods, 2 which reported the sensitivity of a commonly used GDH assay as 87.6% when compared with toxigenic culture, is consistent with concerns of falsely GDH-negative samples raised by the report of Larson et al 48 NovakWeekley et al 34 reported that initial GDH screening failed to identify approximately 15% of samples containing toxigenic C. difficile isolates. In addition, the mean sensitivity of membrane-type GDH assays in the ESCMID survey was only 60% when compared with toxigenic culture, 3 suggesting that GDH screening may not be as highly sensitive as previously assumed.…”
Section: Gdh Assaysmentioning
confidence: 64%
“…Since then, a variety of PCR assays targeting either tcdB or the tcdC regulator gene have been described. 28,34,56 All three FDA-cleared commercial PCR-based assays for C. difficile use tcdB as their major target. Evaluations of several commercial PCR assays 26,34,35 have appeared in the literature, and several investigators 8 -10 have proposed using PCR assays to confirm GDH screening tests in lieu of using EIA assays because of the low sensitivity of the EIA component of the assays.…”
Section: Pcr Assaysmentioning
confidence: 99%
See 3 more Smart Citations